2006
DOI: 10.4049/jimmunol.177.11.7607
|View full text |Cite
|
Sign up to set email alerts
|

ERK5 Activates NF-κB in Leukemic T Cells and Is Essential for Their Growth In Vivo

Abstract: MAPK cascades play a central role in the cellular response to the environment. The pathway involving the MAPK ERK5 mediates growth factor- and stress-induced intracellular signaling that controls proliferation or survival depending upon the cell context. In this study, we show that reducing ERK5 levels with a specific small hairpin RNA 5 (shERK5) reduced cell viability, sensitized cells to death receptor-induced apoptosis, and blocked the palliative effects of phorbol ester in anti-Fas Ab-treated cells. shERK5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 64 publications
7
74
0
Order By: Relevance
“…Previous reports have indicated that ERK5 activation reduces cellular inflammatory responses by inhibiting the NF‐κB pathway 14, 32. In contrast, in the setting of leukemic T lymphocytes33 or acute inflammation induced by Toll‐like receptor ligands or ischemia‐reperfusion injury,34 ERK5 activation enhances NF‐κB signaling. In this study, we showed that anagliptin treatment impaired the activation of the NF‐κB pathway in macrophages in an ERK5‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have indicated that ERK5 activation reduces cellular inflammatory responses by inhibiting the NF‐κB pathway 14, 32. In contrast, in the setting of leukemic T lymphocytes33 or acute inflammation induced by Toll‐like receptor ligands or ischemia‐reperfusion injury,34 ERK5 activation enhances NF‐κB signaling. In this study, we showed that anagliptin treatment impaired the activation of the NF‐κB pathway in macrophages in an ERK5‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we observed that Src and Abl kinases regulate ERK5 activity (Figure 6c). Since no specific inhibitor is currently available, the role for ERK5 was evaluated by downregulating the kinase with a RNA interference approach (Figure 6d) (Garaude et al, 2006). Cells were infected with retroviruses expressing shRNA specific to ERK5 that allows more than 50% reduction in both kinase activity and protein level.…”
Section: Abl Regulates Erk5 Activation For Src-induced Transformationmentioning
confidence: 99%
“…Relative to other tissues, ERK5 is highly expressed in both the thymus and the spleen [21]. In addition, three studies have shown that ERK5 can be activated in T cells downstream of TCR-mediated signalling [28][29][30]. It has also been reported that MEKK2, an activator of the ERK5 pathway, can interact with LAD/RIBP, an Lck-interacting adaptor protein, which is recruited to the TCR complex [18].…”
mentioning
confidence: 99%